2019
DOI: 10.1038/s41598-019-49750-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of Superoxide Dismutases Isolated From A Scuticociliate Parasite: Physiological Role in Oxidative Stress

Abstract: Philasterides dicentrarchi is a free-living microaerophilic scuticociliate that can become a facultative parasite and cause a serious parasitic disease in farmed fish. Both the free-living and parasitic forms of this scuticociliate are exposed to oxidative stress associated with environmental factors and the host immune system. The reactive oxygen species (ROS) generated by the host are neutralized by the ciliate by means of antioxidant defences. In this study we aimed to identify metalloenzymes with superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…For example, it possesses mitochondria with two respiratory pathways: the cytochrome pathway, which exists in all aerobic organisms, and an alternative, cyanide-insensitive oxidase pathway, which enables the ciliate to survive and proliferate under normoxic and hypoxic conditions [ 15 ] and thus to become adapted to differences in oxygen levels in the host and seawater. In addition, P. dicentrarchi has potent antioxidant defence mechanisms that may be important during infection, including several superoxide dismutases that help the ciliate resist the reactive oxygen species released by the host [ 16 ]. Finally, it has been suggested that P. dicentrarchi can release its extrusome contents to create a protective barrier against soluble factors of the host immune system [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it possesses mitochondria with two respiratory pathways: the cytochrome pathway, which exists in all aerobic organisms, and an alternative, cyanide-insensitive oxidase pathway, which enables the ciliate to survive and proliferate under normoxic and hypoxic conditions [ 15 ] and thus to become adapted to differences in oxygen levels in the host and seawater. In addition, P. dicentrarchi has potent antioxidant defence mechanisms that may be important during infection, including several superoxide dismutases that help the ciliate resist the reactive oxygen species released by the host [ 16 ]. Finally, it has been suggested that P. dicentrarchi can release its extrusome contents to create a protective barrier against soluble factors of the host immune system [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For de novo assembly of the parasite genome, the data sets were combined using TULIP software, v0.4 50 . For sequencing of the P. dicentrarchi transcriptome, we followed the RNAseq procedure as previously described 51 , 52 .…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were immunoblotted with a 1: 100 dilution of the anti-rPdVP1 (α-rPdVP1) and anti-KLH-HK (α-KLH-HK) antibodies and then with a polyclonal peroxidase-conjugated rabbit anti-mouse antibody (Dakopatts, Denmark) at 1: 800 dilution. The blots were stained by adding a chromogenic enzyme substrate solution consisting of 0.003% H 2 O 2 and 0.06% 3,30-diaminobenzidine tetrahydrochloride with 0.03% NiCl 2 (DAB/NiCl 2 , Sigma, USA) 51 .…”
Section: Methodsmentioning
confidence: 99%
“…The AOX gene nucleotide sequence was synthesized by Invitro GeneArt Gene Synthesis (ThermoFisher Scientific), amplified by PCR with the primers FaoxKl / RaoxKl: 5′-CGC CTC GAG AAA AGA ATG CAG TCC TTC GCC AGG AAA-3′/5′-ATA AGA ATG CGG CCG C TTA GTG GTG GTG ATG ATG GTG ATG ATG ATG ATG CTG CTC GGG GGA GTA AGG GTT 3′ and cloned in the integrative expression vector pKLAC2. The K. lactis Protein Expression kit (New England Biolabs, UK) was used to express the recombinant protein in yeast according to the manufacturer's instructions and the protein secretion strategy, as previously described 42 .…”
Section: Methodsmentioning
confidence: 99%
“…with 200 µg of rAOX. The antiserum was purified by immobilized metal affinity chromatography (IMAC) with Ni-Sepharose 42 and adsorbed for 30 min at room temperature in 200 µL of a 1% chitosan hydrogel adjuvant 42 (CH) (w/v) in PBS buffer, pH 7.0. At intervals of 15 and 30 days after the first immunization, mice were reimmunized with the same dose of rAOX and adjuvant.…”
Section: Methodsmentioning
confidence: 99%